Study on electronic banking towards customer satisfaction - CHERUKUR, MR. RAM BABU; RUBY, MS. SANDHYA (The journal of contemporary issues in business and government, 2020)
Electronic banking is a form of banking in which funds are transferred through an exchange of electronic signals rather than through an exchange of cash, checks, or other types of paper documents. Transfers of funds occur between financial institutions such as banks and credit union . Electronic banking system has progressed in the recent years . The study is to understand the customer satisfaction in electronic banking . The main reason that electronic banking came into existence is to ease customer money transaction in any time , any place with out visiting the bank . The study is carried by a survey among the electronic bank users to identify the customer satisfaction . A sample of 205 was used to analysis the research .